Prospective Effects of Induced Mutation by Gamma Radiation in Essential Oil Production of Lemongrass (Cymbopogon citratus) - S.A. Sharifah N.R.; A.M. Mahir; C.W.N. C.W.-Zanariah; Kamaruzzaman Jusoff; M.N. Hanina; O Siti Salhah; I. M.Noor (International Journal of Agriculture System, 2013)
This review discusses the prospective effects of induced mutation in lemongrass, Cymbopogon citratus by gamma radiation towards its essential oil production by comparing available literatures on radiation studies in Cymbopogon genus. Previous studies on Cymbopogon mutation breeding program have shown that most of the analyses were limited to physical characteristic observation and concise chemical analysis in their essential oil yield. The issue that comes into view is the on-going things that happen in their essential oil biosynthesis correlated with its biological properties and chemical composition changes. Finding the exact cause of where and how the radiation had triggered the differences in essential oil production between mutant and its control variety need to be studied. This concern possibly could be answered by analysing the changes between both varieties on their interactions within chemical, biological and genetic perspectives. Thus, strong understanding could be build for better analysis in lemongrass mutation breeding.